Uniqueness of sampling site contributions to the total variance of macroinvertebrate communities in the Lower Mekong Basin. (January 2018) - Sor, Ratha; Legendre, Pierre; Lek, Sovan
Abstract: Species co-occurrence and site-specific characteristics have a great influence on biotic community composition at local scales and thus contribute to large variations at broad spatial scales. In this paper, we studied invertebrate communities in 63 river sites of the Lower Mekong Basin (LMB) sampled over 609 thousand km 2 . We identified important macroinvertebrate taxa of the component communities (i.e. annelids, crustaceans, mollusks and insects), and key geo-environmental factors that explained the total variance (BDTotal ) of the communities at large spatial scale. We used the " Species Contributions to Beta Diversity" (SCBD) and " Local Contributions to Beta Diversity" (LCBD) approaches to partition total beta diversity (BDTotal ), identified the important macroinvertebrate taxa (those with high SCBD indices), and estimated the uniqueness of sites in community composition (LCBD indices). SCBD indices showed which taxa were the most important in structuring the four component communities: there were 29 insect taxa, which mainly characterized the upstream sites, and 18 mollusk, 7 annelid and 6 crustacean taxa, which all represented the downstream sites. We used linear regression models to investigate the influence of geo-environmental factors and of component communities on LCBD indices. Our results showed great variation in composition within the LMB (BDTotal  = 0.80 on a 0-to-1 scale). Five sites of the main channel exhibited significant uniqueness (LCBD indices) in community composition. One of them was a hotspot location occupied by a community with exceptional taxonomic composition, which should be protected. Four other sites were degraded by human activity and in need of restoration. Multiple regressions indicated that the global LCBD indices are better explained by the environmental factors, i.e. water conductivity, river depth and Secchi depth (adjusted R 2  = 0.26), than by the geographical factors. Among the component communities, mollusks' and insects' LCBDs were the determinants responsible for the variation in the global LCBD indices (adjusted R 2  = 0.84). The uniqueness in community composition of the sites (i.e. LCBDs) that we estimated provides useful ecological information, which could be used to support restoration and conservation planning for the LMB.